Editorial: Flexibles Lernen an Hochschulen gestalten - Claude Müller; Petra Barthelmess; Christian Berger; Gunter Kucza; Maximilian Müller; Philipp Sieber (Zeitschrift für Hochschulentwicklung, 2019)
Editorial